2023
DOI: 10.1111/exd.14747
|View full text |Cite
|
Sign up to set email alerts
|

The JAK–STAT pathway in keloid pathogenesis: a systematic review with qualitative synthesis

Abstract: Keloid tissues contain inflammatory cells and upregulated pro‐inflammatory cytokines. The Janus kinase (JAK)‐signal transducer and activator of transcription (STAT) pathway mediate cellular responses to these cytokines. We performed a systematic review on the role of the JAK–STAT pathway in keloid pathogenesis and the evidence for JAK–STAT inhibitors in keloid treatment. The search combined the terms (1) keloid and (2) JAK or TYK or STAT and included MeSH terms and synonyms. Two reviewers screened the articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
(335 reference statements)
0
2
0
Order By: Relevance
“…The JAK/STAT pathway regulates a wide range of cellular functions, such as proliferation, differentiation, migration, apoptosis, etc., in response to various cytokines and other stimuli [56]. Recently, as the importance of the JAK-STAT pathway in the pathogenesis of keloids has been recognized, studies targeting this pathway for keloid treatments are expanding [57,58].…”
Section: Janus Kinase (Jak)/signal Transducer and Activator Of Transc...mentioning
confidence: 99%
“…The JAK/STAT pathway regulates a wide range of cellular functions, such as proliferation, differentiation, migration, apoptosis, etc., in response to various cytokines and other stimuli [56]. Recently, as the importance of the JAK-STAT pathway in the pathogenesis of keloids has been recognized, studies targeting this pathway for keloid treatments are expanding [57,58].…”
Section: Janus Kinase (Jak)/signal Transducer and Activator Of Transc...mentioning
confidence: 99%
“…The results demonstrated that patients achieved durable SVR35 (≥35% spleen volume reduction) and improved TSS50 (≥50% reduction in total symptom score) (Harrison et al, 2022a). Moreover, potential natural products such as plant-derived cucurbitacin I and curcumin analogue ASC-J9 could be used as JAK/STAT inhibitors to treat related diseases (Yin et al, 2023), and the small molecule drugs, which screened from the databases (Dogra et al, 2023), targeting JAK/STAT could also be regarded as treatment strategies for related diseases (various organ fibrosis, etc.) (Liu et al, 2023).…”
Section: Combination Therapy With Jak/stat Inhibitorsmentioning
confidence: 99%